REINFORCEMENT OF CHARACTER VALUES IN SOCIAL SCIENCE EDUCATION AT MADRASAH TSANAWIYAH MATHLA’UL ANWAR PONTIANAK - Hana Mauludea; Siswandi Siswandi; Nurhadianto Nurhadianto (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
The purpose of this research is to describe what strengthening character values looks like in Mathla'ul Anwar Pontianak-based social studies education. It is hoped that this description of the educational pattern carried out at the Mathla'ul Anwar Islamic Boarding School can contribute to a learning model that can strengthen the character values of students. This research uses a case study method using data collection techniques as a guide to observation, interviews, and documentation. The analysis was carried out qualitatively based on data found through observations, interviews, and collected documents. The results of this research show that the education pattern carried out by Pesantren Pondok is quite progressive in strengthening character values. During routine recitation activities, ustadz and ustadzah highlight the latest themes in the community. Islamic boarding schools make strict rules in an effort to instill discipline and religious values, but they do not exclude modern elements. When students have good character, social intelligence is created in them so that when they enter society, they still have morals and social insight because they have social intelligence. Mathla'ul Anwar Islamic Boarding School is an Islamic educational institution in Indonesia that is widely known and has an important role in Islamic education. Like other Islamic boarding schools, Mathla'ul Anwar also emphasizes the importance of strengthening character values in the education of his students. Good character values provide a basis for decision-making. Santri who have grown up with values such as justice, sincerity, and responsibility will be more likely to make wise and responsible decisions. The aim of this character education is to form students who not only have good religious knowledge but also have noble personalities, commendable morals, and are able to contribute positively to society. By having good character and implementing positive values in their daily lives, students can create an environment that is harmonious, supports each other, and allows them to develop holistically.